Selective synthesis of phosphate mono-esters with an acidic modified niobium oxide catalyst - Jens Wéry; Sofia Radelicki; Thomas J.N. Hooper; Margot Houbrechts; Kwinten Janssens; Wouter Stuyck; Dimitrios Sakellariou; Dirk E. De Vos (Tetrahedron Green Chem)
The atom-efficient esterification of phosphoric acid was investigated for the selective synthesis of phosphate mono-esters using an acid treated niobium oxide catalyst, avoiding the use of amines as is common in literature. Kinetic studies revealed that the heterogeneous catalyst exhibited higher selectivity for mono-esters compared to homogeneous acid catalysts, as supported by calculation of the relative reactivity of mono-ester and phosphoric acid with different catalysts. To characterize the catalyst, its Hammett acidity value (H0) was determined, while solid state 31P NMR enabled studying the adsorption of H3PO4. Due to the mild acidity of the niobium oxide, alcohols with acid-sensitive functions, including substituted double bonds, could be phosphorylated, enabling the synthesis of surfactants such as oleyl phosphate.